2009
DOI: 10.1007/s00415-009-5098-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and definition of drooling in Parkinson’s disease: a systematic review

Abstract: Drooling (saliva loss) is a frequently reported symptom in patients with Parkinson's disease (PD), but an accurate estimate of the prevalence of drooling is lacking. The aim of this study was to systematically review the prevalence of drooling in published research papers. A systematic PubMed and CINAHL search was done, including studies published until January 2009. Eight studies were found, presenting prevalence rates of drooling based on responses of PD patients to questionnaires. The statistical heterogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
60
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 17 publications
9
60
1
Order By: Relevance
“…However, it was not related to cognition. Diurnal drooling was found to be not rare (23.4%) in our PD patients, which is consistent with a previous study on a Dutch population (28%) [4], but less than the report that the prevalence of all-day drooling (including both diurnal and nocturnal drooling) in PD varied from 32% to 74% [2]. These findings indicate that the prevalence of diurnal drooling may not be as popular as nocturnal drooling in PD.…”
Section: Discussionsupporting
confidence: 90%
“…However, it was not related to cognition. Diurnal drooling was found to be not rare (23.4%) in our PD patients, which is consistent with a previous study on a Dutch population (28%) [4], but less than the report that the prevalence of all-day drooling (including both diurnal and nocturnal drooling) in PD varied from 32% to 74% [2]. These findings indicate that the prevalence of diurnal drooling may not be as popular as nocturnal drooling in PD.…”
Section: Discussionsupporting
confidence: 90%
“…Kalf et al [14] saw the highest prevalence rates in nocturnal drooling (22-26% of PD patients). Prevalence rates were lower in patients with milder PD symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence rates were lower in patients with milder PD symptoms. Their study found that drooling and dementia were present in 50 and 20-40% of all PD patients, respectively [14]. Substantial cognitive impairment and dementia typically occur years after the onset of motor symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Sialorrhea affects up to 78% of patients and is manifested by excessive drooling, which can cause dysphagia and vice versa. The saliva is described as being thick and rope-like, and the leakage may result in coughing and choking, frequent lip wiping, angular cheilitis and increased embarrassment in patients (2,16,23,24,25).…”
Section: Symptoms Of Parkinson`s Disease I S S U E 4 2 0 1mentioning
confidence: 99%